2022
DOI: 10.1002/ncp.10846
|View full text |Cite
|
Sign up to set email alerts
|

Increased nutrition risk at admission is associated with longer hospitalization in children and adolescents with COVID‐19

Abstract: Background: We investigated the association of nutritional risk and inflammatory marker level with length of stay (LOS) in children and adolescents hospitalized for COVID-19 infection in two pediatric teaching hospitals in a developing country. Methods: This was a cross-sectional analytical retrospective study performed in two pediatric hospitals. We included the data from all children and adolescents who were hospitalized with a SARS-CoV-2 infection between March and December 2020. Demographic, anthropometric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 24 publications
2
5
0
Order By: Relevance
“…In the present study, 34% of the evaluated patients were in intensive care, and those who were at high nutritional risk had almost 5 times more chance of ICU admission. The present result is similar to a retrospective study 11 carried out in São Paulo, where 40.5% of patients were admitted to ICU, which was associated with higher nutritional risk by STRONGkids, compared to those with lower nutritional risk [75% vs 28.3%; (p= 0.000)].…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…In the present study, 34% of the evaluated patients were in intensive care, and those who were at high nutritional risk had almost 5 times more chance of ICU admission. The present result is similar to a retrospective study 11 carried out in São Paulo, where 40.5% of patients were admitted to ICU, which was associated with higher nutritional risk by STRONGkids, compared to those with lower nutritional risk [75% vs 28.3%; (p= 0.000)].…”
Section: Discussionsupporting
confidence: 89%
“…Zamberlan and colleagues 11 observed an association between longer hospital stays with higher nutritional risk assessed by STRONGkids, in children and adolescents with COVID-19, where STRONGkids ≥ 4 points was related to a later discharge date ( p = 0.0107). The association between high nutritional risk and lower chance of hospital discharge has already been described in another study 20 that evaluated 641 Brazilian individuals, in the period from 2014 to 2018.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…However, extrapolations from other RNA virus infections, such as the 1918 influenza pandemic, suggest that alterations in nutrition status affected respiratory disease severity and clinical regression 16 . A previous study on COVID‐19 in children demonstrated that high nutrition risk based on STRONG kids (Screening Tool for Risk on Nutritional status and Growth) scores were associated with a longer length of stay 17 . The effect of nutrition risk on time to viral nucleic acid conversion may be that the nutrition status of the organism impairs viral clearance benefits by impairing cell‐mediated immune function, cytokine production, and phagocytosis.…”
Section: Discussionmentioning
confidence: 99%
“…16 A previous study on COVID-19 in children demonstrated that high nutrition risk based on STRONG kids (Screening Tool for Risk on Nutritional status and Growth) scores were associated with a longer length of stay. 17 The effect of nutrition risk on time to viral nucleic acid conversion may be that the nutrition status of the organism impairs viral clearance benefits by impairing cell-mediated immune function, cytokine production, and phagocytosis. In addition, adaptive immunity is influenced by nutrition status, particularly the maturation and differentiation of lymphocytes, the production of memory cells, and the production of cytokines and antibodies.…”
Section: Discussionmentioning
confidence: 99%